Growth and electronic properties of thin Zn layers on Cu(1 1 1) - Ammon, Christian; Held, Georg; Pantförder, Jörg; Steinrück, Hans-Peter (Surface Science, 2001)
The growth and the electronic structure of thin Zn layers on Cu(111) in the coverage range 0 ≤ Θ ≤ 60 ML was studied by temperature-programmed desorption (TPD) of Zn and CO and angle resolved UV-photoelectron spectroscopy (ARUPS). CO titration experiments indicate two-dimensional growth for small amounts of Zn (up to 1 ML) after annealing to 400 K. Upon further annealing, the first Zn layer desorbs over a relatively wide temperature range between 500 and 640 K. For sub-monolayers of Zn an irreversible phase transition is found around 475 K which causes drastic changes in the shape of the CO-TPD spectra from these surfaces. The ARUPS data show a small but clear dispersion of the Zn 3d states for Zn layers above 0.5 ML. The transition at 475 K causes a narrowing of the Zn 3d bandwidth leaving the average binding energy unchanged. This indicates a larger separation of the Zn atoms in this surface arrangement which can be explained by a substitutional adsorption of Zn atoms. © 2001 Elsevier Science B.V. All rights reserved.